The Music Association of Ireland: : Fostering a Voice for Irish Composers and Compositions (Journal of Music Research Online, 2022)
The improvement of conditions for composers in Ireland was one of the primary objectives of the Music Association of Ireland (MAI, founded in 1948). With the presence of composers such as Aloys Fleischmann, Brian Boydell and Frederick May on the MAI’s first Council the plight of the composer in Ireland featured significantly on the MAI’s agenda and activities. The Association sought to develop an audience for modern music and agitated for increased performance, publication and recording opportunities for works by Irish composers. It also attempted to shift Irish contemporary music from its parochial focus towards an international focus.By concentrating on MAI initiatives such as the Composers’ Group (1953–1975) and the Dublin Twentieth Century Music Festival (1969–1986), I expound the major contribution of the MAI in fostering talented Irish composers from its inception and, most importantly, trace its contribution towards the development of a musical infrastructure for indigenous Irish composers. It is unfortunate that these activities have been largely forgotten with improvements credited to more recent professional organisations associated with contemporary music in Ireland today.